Cerebellar Insulin/IGF-1 signaling in diabetic rats: Effects of exercise training. (3rd February 2017) - Borges, Mariana Eiras; Ribeiro, Alessandra Mussi; Pauli, José Rodrigo; Arantes, Luciana Mendonça; Luciano, Eliete; de Moura, Leandro Pereira; de Almeida Leme, José Alexandre Curiacos; Medeiros, Alessandra; Bertolini, Natália Oliveira; Sibuya, Clarice Yoshiko; Gomes, Ricardo José
Highlights: The uncontrolled diabetes mellitus leads to brain changes similar to neurodegenerative diseases like Parkinson's Disease. Aerobic exercise training can be used as treatment and prevention of neurodegeratives diseases, especially in patients with DM. Aerobic training may be able to alters some proteins related to insulin/IGF-1 signaling in cerebellum of DM. Abstract: The Diabetes Mellitus (DM) is a chronic disease associated with loss of brain regions such as the cerebellum, increasing the risk of developing neurodegenerative diseases such as Parkinson's disease (PD). In the brain of diabetic and PD organisms the insulin/IGF-1 signaling is altered. Exercise training is an effective intervention for the prevention of neurodegerative diseases since it release neurotrophic factors and regulating insulin/IGF-1 signaling in the brain. This study aimed to evaluate the proteins involved in the insulin/IGF-1 pathway in the cerebellum of diabetic rats subjected to exercise training protocol. Wistar rats were distributed in four groups: sedentary control (SC), trained control (TC), sedentary diabetic (SD) and trained diabetic (TD). Diabetes was induced by Alloxan (ALX) (32 mg/kg b.w.). The training program consisted in swimming 5 days/week, 1 h/day, during 6 weeks, supporting an overload corresponding to 90% of the anaerobic threshold. At the end, cerebellum was extracted to determinate the protein expression of GSK-3β, IRβ and IGF-1R and the phosphorylation of β-amyloid, Tau, ERK1 + ERK2 by Western Blot analysis. All dependent variables were analyzed by one-way analysis of variance with significance level of 5%. Diabetes causes hyperglycemia in both diabetic groups; however, in TD, there was a reduction in hyperglycemia compared to SD. Diabetes increased Tau and β-amyloid phosphorylation in both SD and TD groups. Furthermore, aerobic exercise increased ERK1 + ERK2 expression in TC. The data showed that in cerebellum of diabetic rats induced by alloxan there are some proteins expression like Parkinson cerebellum increased, and the exercise training was not able to modulate the expression of these proteins.